2010
DOI: 10.1590/s0031-10492010002200001
|View full text |Cite
|
Sign up to set email alerts
|

O conhecimento sobre morcegos (Chiroptera: Mammalia) do estado do Espírito Santo, sudeste do Brasil

Abstract: A Ordem Chiroptera apresenta importância relevante na dinâmica dos ecossistemas, sendo a ordem de mamíferos com maior diversidade de hábitos de vida. Dentre os estados da região Sudeste do Brasil, o Espírito Santo é um dos mais carentes em relação ao conhecimento de morcegos. Este estudo sintetizou o estado do conhecimento sobre quirópteros gerado no Espírito Santo. Para isso, foram catalogados os morcegos depositados no Museu de Biologia Prof. Mello Leitão (MBML), no Laboratório de Estudos de Quirópteros da U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In terms of bat identification, we found a fairly representative number of species. Of the 42 species of Phyllostomidae and ten species of Vespertilionidae that have already been described in ES state [ 42 ], we found 38% and 10%, respectively. We observed that environmental variables interfered with the distributions of the bats, as only 1/3 of the bat species were found at the three study sites.…”
Section: Discussionmentioning
confidence: 71%
“…In terms of bat identification, we found a fairly representative number of species. Of the 42 species of Phyllostomidae and ten species of Vespertilionidae that have already been described in ES state [ 42 ], we found 38% and 10%, respectively. We observed that environmental variables interfered with the distributions of the bats, as only 1/3 of the bat species were found at the three study sites.…”
Section: Discussionmentioning
confidence: 71%
“…However, looking at Ruschi's publications we could not find any references for the presence of T. tricolor or any thyropterid. Mendes et al (2010) reviewed more than 50 papers (including the majority of Ruschi publications) and 14 unpublished works and did not find a record either. Therefore, this new record represents the first documented occurrence of the family Thyropteridae and Thyroptera wynneae for Espírito Santo state.…”
mentioning
confidence: 99%
“…Therefore, this new record represents the first documented occurrence of the family Thyropteridae and Thyroptera wynneae for Espírito Santo state. The species richness for the state is now 77 species, distributed in eight families and 47 genera (Lorenzutti and Almeida 2006;Lira et al 2009;Mendes et al 2010;Pimenta et al 2010;Peracchi et al 2011;Hoppe et al 2014;Pimenta et al 2014). Requena, Jenaro Herrera, Centro de Investigaciones Jenaro Herrera (04°55′ S, 73°40′ W) (Velazco et al 2014).…”
mentioning
confidence: 99%
“…Along its distribution, however, it is a rare to uncommon species (Aguiar et al 2006). In Brazil, few records are available for most states where this bat has been found, and some well-studied states still lack records (e.g., Espírito Santo, Mendes et al 2010). While examining material in a museum mammal collection, we discovered a specimen of D. youngii that fills the gap for the state of Goiás.…”
Section: Introductionmentioning
confidence: 95%